Waste Melting Stove Achieves 25 Kilogram Per Hour Capacity: Kompor Pelebur Sampah Mampu Memproses 25 Kilogram Per Jam - Faris Ferdiansyah; Mulyadi; Edi Widodo; A`rasy Fahruddin (Indonesian Journal of Innovation Studies, 2025)
General Background: Organic waste accumulation presents significant environmental challenges, including methane emissions and pollution. Specific Background: Conventional waste treatment methods often require high energy consumption and incur substantial operational costs. Knowledge Gap: There is limited development of low-cost waste melting systems utilizing alternative fuels such as used oil combined with water to support combustion. Aims: This study aims to design, manufacture, and evaluate the performance of an organic waste melting stove using a mixture of used oil and water. Results: The manufacturing process involves design, material selection, fabrication, assembly, and testing, with a total production time of approximately 635 minutes. The total production cost is calculated at Rp 2,719,100, and the selling price is determined at Rp 3,534,830 with a 30% profit margin. Performance testing shows that a 4 mm nozzle achieves a combustion capacity of 25 kg/hour, while an 8 mm nozzle produces 7 kg/hour. Novelty: The study introduces a waste melting stove integrating alternative fuel from used oil and water with detailed manufacturing cost and performance evaluation. Implications: The system provides a practical and economical solution for organic waste processing and supports sustainable waste management practices. Keywords: Waste Melting Stove, Used Oil Fuel, Combustion Capacity, Manufacturing Cost, Waste Management Key Findings Highlights Fabrication completed within 635 minutes using structured stages Smaller nozzle configuration produced higher burning throughput Economic calculation defined marketable price with profit margin